2022
DOI: 10.3389/fphar.2022.925349
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Reveals Inhibitory Effect of Baicalein on Non-Alcoholic Fatty Liver Disease in Mice

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease, whose etiology is poorly understood. Accumulating evidence indicates that gut microbiota plays an important role in the occurrence and progression of various human diseases, including NAFLD. In this study, NAFLD mouse models were established by feeding a high-fat diet (HFD). Baicalein, a natural flavonoid with multiple biological activities, was administered by gavage, and its protective effect on NAFLD was analyzed by histopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…At the genus and species level, changes in microbiota richness and diversity during NASH were primarily associated with Romboutsia ( Zeng et al., 2019 ), Turicibacter , Lachnoclostridium ( Li et al., 2022 ), Blautia ( Vallianou et al., 2021 ), Ruminococcus_torques_group , Sutterella , Escherichia-Shigella, Prevotella , Alistipe , and Lactobacillus_acidophilus . Escherichia-Shigella produces ethanol that can damage the intestinal mucosa and promote liver inflammation ( Zhu et al., 2013 ), Sutterella has pro-inflammatory effects on the gastrointestinal tract ( Hiippala et al., 2016 ), and Escherichia-Shigella and Sutterella , both belonging to the Proteobacteria phylum, induce LPS biosynthesis ( Song et al., 2017 ; Xu et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the genus and species level, changes in microbiota richness and diversity during NASH were primarily associated with Romboutsia ( Zeng et al., 2019 ), Turicibacter , Lachnoclostridium ( Li et al., 2022 ), Blautia ( Vallianou et al., 2021 ), Ruminococcus_torques_group , Sutterella , Escherichia-Shigella, Prevotella , Alistipe , and Lactobacillus_acidophilus . Escherichia-Shigella produces ethanol that can damage the intestinal mucosa and promote liver inflammation ( Zhu et al., 2013 ), Sutterella has pro-inflammatory effects on the gastrointestinal tract ( Hiippala et al., 2016 ), and Escherichia-Shigella and Sutterella , both belonging to the Proteobacteria phylum, induce LPS biosynthesis ( Song et al., 2017 ; Xu et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota plays an important role in the progression of NAFLD, and gut microbiota dysbiosis is a key factor in NAFLD pathogenesis (30)(31)(32). Based on 16S rRNA gene sequencing analysis, we investigated whether 10.3389/fnut.2022.993501 the gut microbiota was influenced by FDE treatment.…”
Section: Fagopyrum Dibotrys Extract Supplementation Restructures Inte...mentioning
confidence: 99%
“…The combination of multiomics technology can more effectively analyze the potential mechanism of NAFLD. Combined metabolomics and transcriptomics found that Hassk fruit polyphenol extract relieves NAFLD through the TLR4-NKKB pathway and that the positive effect of baicalein on NAFLD may be related to the regulation of lipid metabolism by gut flora …”
Section: Introductionmentioning
confidence: 99%
“…Combined metabolomics and transcriptomics found that Hassk fruit polyphenol extract relieves NAFLD through the TLR4-NKKB pathway 12 and that the positive effect of baicalein on NAFLD may be related to the regulation of lipid metabolism by gut flora. 13 Due to its complex pathogenesis, there are so far no drugs approved to treat NAFLD, although some drugs, such as semaglutide, are undergoing clinical trials. 14 Natural active food ingredients (e.g., polyphenols, saponins, polysaccharides) have been widely studied for their physiological activities on NAFLD.…”
Section: ■ Introductionmentioning
confidence: 99%